Histopathological Features of Early Onset Indonesian Breast Cancer Pointing to Brca1/2 Germline Mutations - Purnomosari Van Der Groep P, Wahyono A, Aryandono T, Pals G, Van Diest PJ (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Breast cancer under 40 years concerns a relatively small subgroup of cases that tend to display a more aggressive phenotype. Compatible with this, early age of onset has been known as one of clinical characteristic of hereditary breast cancers associated with germline BRCA1 or BRCA1 mutations. As early onset breast cancer is frequent in Indonesia, we investigated the histopathological and immunohistochemical characteristics of early onset (< 40 years) Indonesian breast cancer patients, as such features can be used to distinguish between BRCA and non-BRCA germline mutation carriers among these young women.Method: Thirty-five formalin-fixed and paraffin-embedded tissue sections of young women (mean 36 years, range 22-40 years) who underwent surgical resection at the Department of Surgery of the Sardjito Hospital Yogyakarta were examined for pathological features, estrogen and progesterone receptor status, proliferation as determined by Ki67 labeling, EGFR and CK5/6 and the presence of HER-2/neu and p53 protein. Additionally, mutation analysis for BRCA1 and BRCA2 was performed in 30 young women. The control group consisted ofcarcinomas from women above 50 years (mean 59.02, range 50-80 years).Result: Carcinomas occurring in women aged below 40 years were more often advanced stage and higher proliferating (p=0.006). Among the early onset breast cancer patients, ductal type, grade 3, ER and HER-2/neu negativity, high Ki67 index and CK5/6 and EGFR positivity were typical for BRCA1 patients. Unfortunately, there were no typical phenotypical features for BRCA2 carriers. However, grade I and lobular cases were never BRCA1/2 germline mutated.Conclusion: Early onset Indonesian breast cancer shows increased proliferation compared to late onset patients. Within the early onset group, the strongest features pointing to a sporadic cancer seem to be grade I and lobular differentiation. Features increasing the chance of a germline BRCA1/2 mutation are CK5/6 and EGFR expression, p53 accumulation and high proliferation as measured by Ki67 labeling. This is potentially useful to optimize selection of early onset breast cancer patients for BRCA1/2 mutation testing.Keywords: breast cancer, early onset, histopathology, immunohistochemistry, BRCA1, BRCA2